Omar Effendi vs. Union Fenosa: Corruption as a Transnational Public Policy Consideration - Badr Eldin, Ahmed (AUC Knowledge Fountain, 2022)
At the beginning of 2011, Egypt witnessed radical political developments that led to the emergence of a pressing tendency to adjudicate the collapsed regime’s policies and practices. Shortly thereafter, the Egyptian State Council issued a number of judicial decisions that confirmed that the sale of the privatized governmental enterprises had been tainted by corruption. Crucially, the Court maintained that flagrant breach of law, regulations, and administrative orders that encompassed these transactions created serious suspicions about corruption committed by public officials and investors. It concluded that the existence of corruption, as a transnational public policy consideration, had deprived foreign investors of the opportunity to resort to international arbitration. Beyond that, it affirmed that its decisions aimed at protecting the state’s wealth and economy, and encouraging serious investments. However, when Egypt, upon nearly identical circumstantial evidence invoked the issue of corruption as a public policy consideration before ICSID arbitration, it was discarded due to lack of evidence. This paper compares the position of both the national court and the international arbitral tribunal when allegations of corruption, as a transnational public policy consideration, are raised. The study believes that the Court reversed fundamental legal principles of the national law, and maneuvered the concept of transnational public policy to produce a plausible, yet not sound conclusion in the realm of both the national judicial system and international arbitration. Further, this paper suggests that the court’s attempt to safeguarding the Country’s public wealth actually jeopardized justice, the state’s economy, and its investment credibility.